PROTOTYPING MISALIGNMENT MEASUREMENT SYSTEM USING ARDUINO AND MATLAB - Ajie Pratama, Wahyu
Misalignment occurs when two paired engine shafts are not aligned. To avoid serious consequences due to misalignment, the shafts must be corrected by conducting alignment. This action comprises two sequential steps, namely measurement and correction step. Typically, the measurement is performed using laser or dial indicator. Lasers offers two main advantages, which are good accuracy practicality. The practicality is mainly served by the integrated software, on which the raw data is automatically interpreted. Thus, the system avoids data misinterpretation as potentially happens in dial-indicator-based measurement system. However, laser costs much higher than dial indicator. In the measurement system, the hardware is constructed using digital dial indicator and MPU6050 angle sensor. Both sensors are connected to a microcontroller system so that the data can be sent to a computer and further processing can be carried out. After the hardware is built, the research is continued by developing software under Matlab environment. This software is designed to convert raw data into a two-dimensional display that interprets the position of the shafts. Based on the experiment, it can be concluded that the system reads signals from the dial indicator and angle sensors properly. In addition, the software provides a graphical interpretation that is exactly the same as the interpretation obtained through manual calculations.